Information and communication on technology for the fight against global warming first international conference, ICT-GLOW 2011, Toulouse, France, August 30-31, 2011, proceedings - ICT-GLOW (Conference) 2011 Toulouse, France); Kranzlmüller, Dieter; Toja, A Min.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the First International Conference on Information and Communication Technology for the Fight against Global Warming, ICT-Glow 2011, held in Toulouse, France in August 2011. The 16 revised papers presented were carefully reviewed and selected from 24 submissions. They address the following topics: parallel computing, ICT for transportation, cloud and pervasive computing, measurement and control and storage.
International conference proceedings.
Electronic reproduction.
Keywords: Information technology -- Environmental aspects -- Congresses; Global warming -- Technological innovations -- Congresses; Global warming -- Congresses; Green technology -- Congresses; Electronic books